Transfusion reaction in a case with the rare Bombay blood group - Shahshahani, Hayedeh Javadzadeh (Medknow Publications & Media Pvt Ltd, 2013)
Bombay phenotype is extremely rare in Caucasian with an incidence of 1 in 250,000. When individuals with the Bombay phenotype need blood transfusion, they can receive only autologous blood or blood from another Bombay blood group. Transfusing blood group O red cells to them can cause a fatal hemolytic transfusion reaction. In this study, we report a case with the rare Bombay blood group that was misdiagnosed as the O blood group and developed a hemolytic transfusion reaction. This highlights the importance of both forward and reverse typing in ABO blood grouping and standard cross-matching and performing standard pretransfusion laboratory tests in hospital blood banks.